Redox-active tetrathiafulvalene and dithiolene compounds derived from allylic 1,4-diol rearrangement products of disubstituted 1,3-dithiole derivatives - Vilela, Filipe; Skabara, Peter J.; Mason, Christopher R.; Westgate, Thomas D. J.; Luquin, Asun; Coles, Simon J.; Hursthouse, Michael B. (Beilstein Journal of Organic Chemistry, 2010)
We present a series of compounds by exploiting the unusual 1,4-aryl shift observed for electron-rich 1,3-dithiole-2-thione and tetrathiafulvalene (TTF) derivatives in the presence of perchloric acid. The mechanistic features of this rearrangement are discussed since this synthetic strategy provides an alternative route for the synthesis and functionalisation of sulfur rich compounds including redox active compounds of TTFs, and a Ni dithiolene.
Keywords: aldehydes; metal-coordination; rearrangement; sulfur heterocycles; tetrathiafulvalene

(untitled) - Christensen, C. A.; Batsanov, A. S.; Bryce, M. R. (J. Am. Chem. Soc., 2006)

(untitled) - Perez, E. M.; Sierra, M.; Sanchez, L.; Torres, M. R.; Viruela, R.; Viruela, P. M.; Orti, E.; Martin, N. (Angew. Chem., Int. Ed., 2007)

(untitled) - Svenstrup, N.; Becher, J. (Synthesis, 1995)

(untitled) - Khan, T.; Skabara, P. J.; Coles, S. J.; Hursthouse, M. B. (Chem. Commun., 2001)

(untitled) - Kanibolotsky, A. L.; Forgie, J. C.; Gordeyev, S.; Vilela, F.; Skabara, P. J.; Lohr, J. E.; Petersen, B. M.; Jeppesen, J. O. (Macromol. Rapid Commun., 2008)

(untitled) - Serebryakov, I. M.; Skabara, P. J.; Perepichka, I. F. (J. Chem. Soc., Perkin Trans. 2, 1999)

(untitled) - Young, W. G.; Nozaki, K.; Warner, R. (J. Am. Chem. Soc., 1939)

(untitled) - Marion, N.; Gealageas, R.; Nolan, S. P. (Org. Lett., 2007)

(untitled) - Young, W. G.; Winstein, S.; Goering, H. L. (J. Am. Chem. Soc., 1951)

(untitled) - Zhang, L.; Zhou, W.-S.; Xu, X.-X. (Chem. Commun., 1988)

(untitled) - Aitken, R. A.; Garnett, A. N. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Wu, L.; Shi, M.; Li, Y. X. (Chem.–Eur. J., 2010)

(untitled) - Kirmse, W.; Guenther, B.-R. (J. Am. Chem. Soc., 1978)

(untitled) - del Rio, E.; Menédez, M. I.; López, R.; Sordo, T. L. (J. Phys. Chem. A, 2000)

(untitled) - Nakanishi, W.; Hayashi, S.; Arai, T. (Chem. Commun., 2002)

(untitled) - Khan, T.; McDouall, J. J. W.; McInnes, E. J. L.; Skabara, P. J.; Frère, P.; Coles, S. J.; Hursthouse, M. B. (J. Mater. Chem., 2003)

(untitled) - Fourmigué, M.; Krebs, F. C.; Larsen, J. (Synthesis, 1993)

(untitled) - Bryce, M. R.; Skabara, P. J.; Moore, A. J.; Batsanov, A. S.; Howard, A. K.; Hoy, V. J. (Tetrahedron, 1997)

(untitled) - Le Derf, F.; Mazari, M.; Mercier, N.; Levillain, E.; Trippé, G.; Riou, A.; Richomme, P.; Becher, J.; Garín, J.; Orduna, J.; Gallego-Planas, N.; Gorgues, A.; et al. (Chem.–Eur. J., 2001)

(untitled) - Allen, F. H.; Kennard, O.; Watson, D. G.; Brammer, L.; Orpen, A. G.; Taylor, R. (J. Chem. Soc., Perkin Trans. 2, 1987)

(untitled) - Leufgen, M.; Rost, O.; Gould, C.; Schmidt, G.; Geurts, J.; Molenkamp, L. W.; Oxtoby, N. S.; Mas-Torrent, M.; Crivillers, N.; Veciana, J.; Rovira, C. (Org. Electron., 2008)

(untitled) - Mas-Torrent, M.; Masirek, S.; Hadley, P.; Crivillers, N.; Oxtoby, N. S.; Reuter, P.; Veciana, J.; Rovira, C.; Tracz, A. (Org. Electron., 2008)

(untitled) - Mas-Torrent, M.; Durkut, M.; Hadley, P.; Ribas, X.; Rovira, C. (J. Am. Chem. Soc., 2004)

(untitled) - Rovira, C. (Chem. Rev., 2004)

(untitled) - Mas-Torrent, M.; Rovira, C. (J. Mater. Chem., 2006)

(untitled) - Kato, R. (Chem. Rev., 2004)

(untitled) - Pozo-Gonzalo, C.; Berridge, R.; Skabara, P. J.; Cerrada, E.; Laguna, M.; Coles, S. J.; Hursthouse, M. B. (Chem. Commun., 2002)

(untitled) - Skabara, P. J.; Pozo-Gonzalo, C.; Miazza, N. L.; Laguna, M.; Cerrada, E.; Luquin, A.; González, B.; Coles, S. J.; Hursthouse, M. B.; Harrington, R. W.; Clegg, W. (Dalton Trans., 2008)

(untitled) - Anthopoulos, T. D.; Setayesh, S.; Smits, E.; Colle, M.; Cantatore, E.; de Boer, B.; Blom, P. W. M.; de Leeuw, D. M. (Adv. Mater., 2006)

(untitled) - Pozo-Gonzalo, C.; Roberts, D. M.; Skabara, P. J. (Synth. Met., 2001)

(untitled) - Pozo-Gonzalo, C.; Khan, T.; McDouall, J. J. W.; Skabara, P. J.; Roberts, D. M.; Coles, S. J.; Hursthouse, M. B.; Neugebauer, H.; Cravino, A.; Sariciftci, N. S. (J. Mater. Chem., 2002)

(untitled) - Blessing, R. H. (Acta Crystallogr., 1995)

(untitled) - Blessing, R. H. (J. Appl. Crystallogr., 1997)

SHELX97 (Sheldrick, G. M.; University of Göttingen, 1997)